Electro and electro-photo plasticity of CdZnTeSe and CdZnTe. (March 2023) - Dědič, Václav; Franc, Jan; Moravec, Pavel; Grill, Roman; Elhadidy, Hassan; Šíma, Vladimír; Cieslar, Miroslav; Roy, Utpal N.; James, Ralph B.
Abstract: We studied the influence of applied bias on of the Vickers microhardness HV 0.025 of CdZnTeSe and CdZnTe semi-insulating samples without and with the illumination of light at 870 nm. We observed that a small applied bias results in the hardening of the material. The effect is strongest at a bias of ± 0.5 V and is further strengthened by additional illumination. We suggest that the observed positive electro and electro-photo plastic effects in CdZnTeSe and CdZnTe can be explained by an increase in the concentration of free electrons and holes injected from contacts in a biased sample or generated by illumination. These free carriers can be trapped at dislocations and induce a reconstruction of bonds at the dislocation core. The necessity to break the bonds before dislocation glide results in an increase of microhardness. Graphical Abstract: ga1